A 3D bioprinted nano-laponite hydrogel construct promotes osteogenesis by activating PI3K/AKT signaling pathway. (December 2022) - Miao, Sheng; Zhou, Jinru; Liu, Bin; Lei, Xing; Wang, Taoran; Hao, Xiaotian; Cheng, Pengzhen; Wu, Hao; Song, Yue; Pei, Guoxian; Bi, Long
Abstract: Development of nano-laponite as bioinks based on cell-loaded hydrogels has recently attracted significant attention for promoting bone defect repairs and regeneration. However, the underlying mechanisms of the positive function of laponite in hydrogel was not fully explored. In this study, the effect of 3D bioprinted nano-laponite hydrogel construct on bone regeneration and the potential mechanism was explored in vitro and in vivo . In vitro analyses showed that the 3D construct protected encapsulated cells from shear stresses during bioprinting, promoted cell growth and cell spreading, and BMSCs at a density of 10 7 /mL exhibited an optimal osteogenesis potential. Osteogenic differentiation and ectopic bone formation of BMSCs encapsulated inside the 3D construct were explored by determination of calcium deposition and x-ray, micro-CT analysis, respectively. RNA sequencing revealed that activation of PI3K/AKT signaling pathway of BMSCs inside the laponite hydrogel significantly upregulated expression of osteogenic related proteins. Expression of osteogenic proteins was significantly downregulated when the PI3K/AKT pathway was inhibited. The 3D bioprinted nano-laponite hydrogel construct exhibited a superior ability for bone regeneration in rat bones with defects compared with groups without laponite as shown by micro-CT and histological examination, while the osteogenesis activity was weakened by applications of a PI3K inhibitor. In summary, the 3D bioprinted nano-laponite hydrogel construct promoted bone osteogenesis by promoting cell proliferation, differentiation through activation of the PI3K/AKT signaling pathway. Graphical abstract: Figure: Nano-laponite hydrogel construct with BMSCs was bioprinted. The construct was mineralized after in vitro culture, ectopically generated bone in the muscle pouch. In addition, it was able to promote repair of calvarial defect accompanied by elevation of pi3k and akt. Image 1